The Influence of Brand Image, Brand Trust and Product Quality on Purchasing Decisions on PT. BS Motorcycle Products Esaf Frame - Istiqomah, Mira; Sarah, Siti (Dinasti Publisher, 2023)
In the current era of globalization which is very rapidly developing, causing changes in lifestyle in humans who want to be fast-paced and practical is to increase purchasing decisions for BS motorcycle products, two-wheeled vehicles which are a means of transportation that is easily used by all groups and can reach difficult places. aspects to improve purchasing decisions for brand image, brad trust, and product quality, so that purchasing decisions run optimally. The purpose of this study was to determine brand image, brad trust and product quality on purchasing decisions for BS motorcycle products. The research method used is quantitative research method with descriptive and verification approaches. The results showed that: (1) the decision to purchase a BS motorcycle is in the unfavorable category. (2) Brand image of BS motorcycle products in the unfavorable category (3) Brand trust of BS motorcycle products in the unfavorable category. (4) The quality of BS motorcycle products is in the unfavorable category (5) Partially Brand Image has a positive effect on Purchasing Decisions for BS motorcycle products for Consumers. (6) Partially, brand trust has a positive effect on the decision to buy PT BS motorcycle products. (7) Partially product quality has a positive influence on purchasing decisions. (8) Partially Simultaneously Brand Image, Brand Trust and product quality have a positive influence on purchasing decisions